MODEL PENGEMBANGAN PEMBELAJARAN IPS BERBASIS KEWIRAUSAHAAN - Rosalia Susila Purwanti Tri Siwi Nugrahani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
Teaching social studies in elementary school should produce students have a sense of empathy with the surrounding environment. But the teacher difficulties with the issue implies a concrete example. One of the reasons for lack of teachers have insight into the business world because of the limitations of the design of the corresponding IPS IPS degan learning objectives. If the teaching of social studies in elementary school using the theme of entrepreneurship will produce a way of teaching that is quite interesting, creative, and realistic. The purpose of the development model of learning social studies course on IPS 2 of this order PGSD students in carrying out the teaching of social studies in elementary school, among others: 1) understand the material IPS 2-minded entrepreneurship, 2) produce teaching materials IPS 2-minded entrepreneurship, and 3) introducing early life entrepreneurship in elementary students, and 4) to teach social studies in elementary students in accordance with the mindset of elementary school children with material that can inspire students to be able to creativity, and independent. Preparation of a draft study on the entrepreneurial-minded IIPS 2 course is tailored to the needs of elementary students with attention: inputs, processes, outputs, and outcomes. Input activity includes determination of material IPS with the theme of entrepreneurship, the process includes the manufacturing scenario in elementary social studies lesson on the theme of entrepreneurship, the output will produce teaching materials IPS, and outcome in elementary students to think critically and have the independence.